DYNAMIC SYSTEM SIMULATION TO IMPROVE SUPPLY CHAIN PERFORMANCE IN FOOD AND BAVERAGE COMPANIES - Sylvia; Ahmad; Kosasih, Wilson (Universitas Tarumanagara, 2025)
In facing increasingly competitive business competition, food and beverage companies are required to improve production efficiency and maintain supply chain resilience in order to achieve optimal production targets. This study was conducted to identify the factors causing the discrepancy between targets and actual production results, evaluate supply chain performance, and simulate improvement scenarios using dynamic systems. The Supply Chain Operation Reference (SCOR) approach is used as a framework in analyzing and identifying critical points in the supply chain. Furthermore, performance measurement is carried out using the Snorm De Boer method to assess performance and determine indicators that require improvement. Scenario simulations were carried out using Powersim Studio 10 to test the influence of various variables. Based on the results of the simulation and ANOVA statistical testing, the best scenario for reducing product defects from the production line is scenario 3 and the best scenario for reducing SBL downtime is scenario 2. And when viewed as a whole, scenario 5 is the most balanced scenario because it is able to reduce SBL downtime by 1.82% and reduce product defects from the production line by 1.19%, thus providing a positive impact in a balanced way on operational efficiency and production quality. This research is expected to be a reference in making strategic company decisions and developing supply chain evaluation methods in the future.